Use of immigration status for coercive control in domestic violence protection orders - Alsinai, Aisha; Reygers, Max; DiMascolo, Lisa; Kafka, Julie; Rowhani-Rahbar, Ali; Adhia, Avanti; Bowen, Deirdre; Shanahan, Sandra; Dalve, Kimberly; Ellyson, Alice M. (Frontiers in Sociology, 2023)
In the context of domestic violence (DV), immigration-related circumstances can be exploited by an abuser to coerce and manipulate their partner. We conducted a textual analysis to describe how immigration-related circumstances were used in threats, coercive control, and acts of violence in a random sample of petitioners who were granted a Domestic Violence Protection Order (DVPO) in King County, WA (n=3,579) from 2014-2016 and 2018-2020. We hand-reviewed textual petitioner narratives and identified n=39 cases that discussed immigration-related circumstances and related acts of violence and coercion by the abusive party. This included threats to contact authorities to interfere with an ongoing immigration process, deportation threats, and threats that would separate families. In many cases, petitioners indicated that immigration-related threats prevented them from leaving the violent partner, seeking help, or reporting the abuse. We also found mention of barriers for victims to receive protection and autonomy from further abuse including a lack of familiarity with US protections and laws, and restrictions on authorizations to work. These findings demonstrate that immigration-specific threats and forms of retaliation undermine survivors and should be recognized by advocates and other legal practitioners to address the distinct needs of petitioners from immigrant communities.